2012
DOI: 10.1063/1.4737635
|View full text |Cite
|
Sign up to set email alerts
|

Trapping in dendrimers and regular hyperbranched polymers

Abstract: Dendrimers and regular hyperbranched polymers are two classic families of macromolecules, which can be modeled by Cayley trees and Vicsek fractals, respectively. In this paper, we study the trapping problem in Cayley trees and Vicsek fractals with different underlying geometries, focusing on a particular case with a perfect trap located at the central node. For both networks, we derive the exact analytic formulas in terms of the network size for the average trapping time (ATT)-the average of node-to-trap mean … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 57 publications
0
68
0
1
Order By: Relevance
“…(14) in Ref. [44] about PMFPT of Cayley tree, we have the leading asymptotic term of ATT with trap located in central node in C g…”
Section: Average Trapping Time On Husimi Cactusmentioning
confidence: 97%
See 1 more Smart Citation
“…(14) in Ref. [44] about PMFPT of Cayley tree, we have the leading asymptotic term of ATT with trap located in central node in C g…”
Section: Average Trapping Time On Husimi Cactusmentioning
confidence: 97%
“…As a representative network, dendrimer (also called Cayley tree) [30][31][32][33][34] has extensive applications in different fields, including medicinal and diagnosis [35,36], drug delivery system [37,38], light harvesting [39,40] and electronic applications [41]. Random walks on dendrimer have been widely studied [42][43][44][45]. During the transport processes, the excitations are usually located on the chromophores of dendrimer or the segments connecting the chromophores [46].…”
Section: Introductionmentioning
confidence: 99%
“…During the past years significant efforts have been devoted to trapping issue in diverse networked a) Electronic mail: zhangzz@fudan.edu.cn; http://www.researcherid.com/rid/G-5522-2011 systems with particular structural properties, such as square-planar lattices and cubic lattices 19,20 , Sierpinski gasket 21,22 and Sierpinski tower 23 , T −shape fractal and its extensions [24][25][26][27][28][29] , dendrimers [30][31][32][33] , hyperbranched polymers 32,33 , non-fractal [34][35][36] and fractal scale-free networks [37][38][39] . These works showed that topological properties crucially affect the trapping efficiency measured by ATT, which can display superlinear, linear, sublinear, logarithmical and other dependence on the system size, depending on network structure.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [42][43][44][45] , MFPT from any node to the central node, as well as the ATT to the center, were deduced. These a) Electronic mail: zhangzz@fudan.edu.cn; http://www.researcherid.com/rid/G-5522-2011 works unveiled the effect of structure on the MFPT and ATT to the central node.…”
Section: Introductionmentioning
confidence: 99%